A Study on the Acquisition of Paralinguistic Features of Oral Presentation Skills Challenges to the Rural Students - Devika, (JOURNAL OF INDIAN EDUCATION, 2017)
Acquisition of second language (L2) has always been challenging; the related theories and proposed ways to help students understand, grasp and use L2 for expression keep evolving. The present paper focuses on the problems faced by rural students while practicing oral presentation. The oral presentations of the rural students (classes IX, X, XI and XII) enrolled in Pilani schools and nearby village schools were recorded and played for them to observe themselves. The students seemed to be keenly observant about the areas of improvement. Learners use a language better when they get to know the specific areas of problem and an explanation for each digression. Hence, the paper also focuses on how these errors, especially regarding paralinguistic features, are committed and how awareness can help these students polish their oral presentation skills.